2018
DOI: 10.7150/thno.19010
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Vascular Shutdown and Cell Death Following Ultrasound-Microbubble Enhanced Radiation Therapy

Abstract: High-dose radiotherapy effects are regulated by acute tumour endothelial cell death followed by rapid tumour cell death instead of canonical DNA break damage. Pre-treatment with ultrasound-stimulated microbubbles (USMB) has enabled higher-dose radiation effects with conventional radiation doses. This study aimed to confirm acute and longitudinal relationships between vascular shutdown and tumour cell death following radiation and USMB in a wild type murine fibrosarcoma model using in vivo imaging.Methods: Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…Several studies have demonstrated that combining low-intensity focused ultrasound with MBs is an effective radiosensitization method. This approach has significantly reduced the radiation dose required for killing tumors in prostate cancer [39], fibrosarcoma [40], and bladder cancer [41]. In those previous studies, after injecting MBs, xenograft tumors were exposed to a 16-cycle, 50-ms tone burst with a center frequency of 500 kHz and a PRF of 3 kHz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that combining low-intensity focused ultrasound with MBs is an effective radiosensitization method. This approach has significantly reduced the radiation dose required for killing tumors in prostate cancer [39], fibrosarcoma [40], and bladder cancer [41]. In those previous studies, after injecting MBs, xenograft tumors were exposed to a 16-cycle, 50-ms tone burst with a center frequency of 500 kHz and a PRF of 3 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…In those previous studies, after injecting MBs, xenograft tumors were exposed to a 16-cycle, 50-ms tone burst with a center frequency of 500 kHz and a PRF of 3 kHz. The treatments lasted for 5 min and the ultrasound peak negative pressure was 0.570 MPa [39][40][41]. Together with MBs, the ultrasound-induced vascular damage greatly enhanced the radiation effect, making a daily radiation dose of 2 Gy as effective as an ablative dose of 8 Gy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, results have demonstrated that endothelial cell death in response to this treatment is predominantly dependent on ceramide production through acid sphingomyelinase (ASMase) signalling [31,32]. Furthermore, acute vascular shutdown and significant tumor cell death is observed [33,34], indicating that tumor cell death is secondary to endothelial cell death. Several in vivo studies have also indicated the effectiveness of this therapy in treating xenograft tumors in murine models, including breast, prostate liver, and bladder [21,22,[35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…This platform utilizes a multi-purpose gas-filled microsphere (microbubble) which carries the therapeutic on the shell, serves as an ultrasound imaging contrast agent, and can facilitate trans-membrane transport of drugs and genes in response to ultrasound 31-33. As intravenously injected microbubbles transit though the microcirculation of the target tissue, ultrasound directed at the target tissue causes microbubble destruction or cavitation and payload release, and enhances vascular permeability and cell membrane permeability only at the target site 34-36. This approach allows for repeated administration of targeted molecular therapeutics without the use of viral vectors.…”
Section: Introductionmentioning
confidence: 99%